Uji Toleransi Tanaman Kentang Hitam (Plectranthus rotundifolius (Poir.) Spreng.) Hasil Radiasi Sinar Gamma terhadap Cekaman Kekeringan - Ridwan, Ridwan; Handayani, Tri; Witjaksono, Witjaksono (JURNAL BIOLOGI INDONESIA, 2016)
Plectranthus rotundifolius (Poir.) Spreng. is one of the potential root crops to become an alternative food. The aim of thisstudy was to determine drought resistant status of Plectranthus rotundifolius irradiated by gamma irradiation. Thisexperiment was conducted in the Green House using a Completely Randomized Design with 2 factors and 5 replications.The first factor was plant number consisted of 7 accessions (D116, D69, M343, D40, M95, D3, and Klefa Imut/KI). Thesecond factor was the level of field capacity (FC) consisted of 100% FC, 60% FC, and 20% FC. The observed parameterwere vegetative and generative growth stage, stomatal conductance, leaf water potential, and chlorophyll content. The resultshowed that the resistance level of the 7 accessions can be devided into 3 categories: 1) The plants that were susceptible todrought i.e. D116, D69, M343, and KI; 2) The plants that were semi-tolerant to drought i.e. D40 and M95; and 3) The plantthat was tolerant to drought i.e. D3.Keywords: Plectranthus rotundifolius, gamma irradiation, drought stress